PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BERKAT ACI MULIA SEMARANG - Siti Abdillah Nurhidayah; Dewi Ressa Utami; Lukman Zaini Abdullah (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2023)
PT. Berkat to Aci Mulia Semarang. This type of research is quantitative research. The sample in this study amounted to 300 respondents and then a sample of 100 respondents was taken using the Solvin formula. In this study using a simple random sampling method, the data collection technique was carried out randomly without regard to the existing strata in the population. The results of this study indicate that: (1) the t test partially the work environment has a positive and significant effect on employee performance. This is evidenced by the results of tcount 3.944 > ttable 1.661, a significance value of 0.000 <0.05. (2) Partially work discipline has a positive and significant effect on employee performance variables. This is evidenced by the results of tcount 6.791 > ttable 1.661 a significance value of 0.000 <0.05. The results of the F test simultaneously have a positive and significant effect on employee performance with a value of fcount 99.129> ftable 3.09. And the results of the test for the coefficient of determination R Squerese is 0.671 which indicates that 67.1% of employee performance is influenced by the work environment and work discipline while the remaining 32.9% is explained by other variables not examined in this study.